The concept of the sakinah family in the perspective of the Qur'an - Khaled, Nashwan Abdo (2021)
Talking about the family in general and the family’s tranquility (Sakinah Family) in particular is of great importance, as the family is the first building block from the Qur’anic point of view, and one of the most important objectives (Maqasid) that Sharia came to achieve, as Sharia came to preserve the honor and preserve regeneration, and both objectives are the main focus of the family. Regeneration: Islam came to protect human regeneration by encouraging marriage, and preventing any relationship outside the fence of the family. Therefore, I am going to limit my presentation with the Quranic perspective on Sakinah family, Although there are many perspectives such as-Sunnah perspective Shairah perspective, the sociological perspective, and other perspectives.